Association Between Prognostic Nutritional Index and Prognosis in Patients With Heart Failure: A Meta-Analysis - Chen, Mei-Yu; Wen, Jiang-Xiong; Lu, Mei-Ting; Jian, Xiang-Yu; Wan, Xiao-Liang; Xu, Zhi-Wen; Liang, Jian-Qiu; Wu, Jian-Di (Frontiers in Cardiovascular Medicine, 2022)
Background: The prognostic nutritional index (PNI) has been proposed as a marker of malnutrition and associated with the prognosis of cardiovascular disease. However, whether PNI can serve as a potential biomarker for the prognosis of heart failure (HF) upon those established risk factors were still controversial. This meta-analysis aimed to generate comprehensive evidence on the prognostic value of PNI in patients with HF. Methods: Multiple databases (PubMed, Embase, the Cochrane Library and Google Scholar) were searched for related studies up to January 31, 2022. Observational studies accessed associations between PNI levels and the prognosis in HF patients were included for meta-analysis. The hazard ratios (HRs) and 95% confidence intervals (CI) were calculated. Results: Fourteen studies, comprising 19,605 patients with HF were included for meta-analysis. The median follow-up duration was 18.5 months. Compared with those with higher PNI (normal nutritional status), HF patients with lower PNI (malnourished) were associated with a higher risk of all-cause mortality (HR 1.53, 95% CI 1.27-1.85) and composite major adverse cardiac outcomes (MACEs) (HR 2.26, 95% CI 1.54-3.31) in the multivariable-adjusted model. Furthermore, when PNI was defined as per 1 increment as a continuous metric, higher PNI was associated with a decrease in all-cause mortality (per 1 increment of PNI: HR 0.94, 95% CI 0.88-0.96) and MACEs (per 1 increment of PNI: HR 0.97, 95% CI 0.95-0.98). Conclusions: PNI can serve as an easily calculated bedside “malnutrition-inflammation” biomarker in HF. Lower PNI was associated with a worse prognosis in patients with HF.